Asia-Pacific economic cooperation (APEC) international grant - Putra Mohd Darul Ridzuan, Rosli (Penerbit UMP, 2014)
The APEC International Grant is a fund by Asia-Pacific Economic Coopertaion or APEC. APEC is a forum to promote growth in economy, cooperation, trade and investment in the Asia Pacific region. It is also aimed at strengthening ties among the community in the region that includes its 21 member countries such as Australia, Brunei Darussalam, Canada, Chile, People's Republic of China, Hong Kong, China, Indonesia, Japan, Republic of Korea, Malaysia, Mexico, New Zealand, Papua New Guinea, Peru, The Republic of the Philippines, The Russian Federation, Singapor, Chinese Taipei, Thailand, United States of America and Viet Nam.